2004
DOI: 10.1897/02-430
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of humic acids and salinity on solid‐phase microextraction of DDT and chlorpyrifos, an estimator of their bioavailability

Abstract: The unbound portion of dissolved hydrophobic environmental contaminants generally is presumed to be the most bioavailable to aquatic organisms. The effects of differing concentrations of Aldrich humic acid (HA) and salinity on the freely dissolved fraction of chlorpyrifos (CPF) and 4,4'-dichlorodiphenyltrichloroethane (DDT) in water were assessed through their relative uptake by solid-phase microextraction (SPME). This extraction method has been recently suggested as a valuable biomimetic tool. Increasing sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…As the overall charge of humic acids at pH 7.0 is larger than that at pH 6.0, the binding of BPA to humic acids is relatively strong at pH 6.0 and thus the free fraction of BPA at pH 6.0 is lower than that at pH 7.0. Keeping the same humic acids concentrations and pH 7.0, the increase of sodium phosphate buffer from 5 mM to 125 mM resulted in higher freely dissolved fraction of BPA, i.e., the binding of BPA to humic acids was reduced with the increase of salinity, which is in agreement with early studies about nonpolar compounds (Schlautman and Morgan, 1993;Jones and Tiller, 1999;Mezin and Hale, 2004). Fig.…”
Section: Combined Effects Of Humic Acids With Salinity and Phsupporting
confidence: 88%
See 1 more Smart Citation
“…As the overall charge of humic acids at pH 7.0 is larger than that at pH 6.0, the binding of BPA to humic acids is relatively strong at pH 6.0 and thus the free fraction of BPA at pH 6.0 is lower than that at pH 7.0. Keeping the same humic acids concentrations and pH 7.0, the increase of sodium phosphate buffer from 5 mM to 125 mM resulted in higher freely dissolved fraction of BPA, i.e., the binding of BPA to humic acids was reduced with the increase of salinity, which is in agreement with early studies about nonpolar compounds (Schlautman and Morgan, 1993;Jones and Tiller, 1999;Mezin and Hale, 2004). Fig.…”
Section: Combined Effects Of Humic Acids With Salinity and Phsupporting
confidence: 88%
“…The environmental pH can affect the ionization of DOM (Jota and Hassett, 1991) and thus influence the binding of neutral hydrophobic compounds to DOM (Paolis and Kukkonen, 1997 ions used to control the ionic strength and the properties of DOM, the ionic strength or salinity can increase (Gauthier et al, 1986;Jota and Hassett, 1991;Brunk et al, 1997) or decrease (Schlautman and Morgan, 1993;Jones and Tiller, 1999) the association of DOM with polychlorinated biphenyls (PCBs) or polycyclic aromatic hydrocarbons (PAHs). By using negligible-depletion solid-phase microextraction (nd-SPME), a biomimetic tool, the combined effects of humic acids and salinity on the availability of 4,4 0 -dichlorodiphenyltrichloroethane (DDT) and chlorpyrifos pesticides were investigated, and it was reported that the binding of DDT and chlorpyrifos by humic acids was greatly reduced with the presence of salt (Mezin and Hale, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been shown for pesticides, including DDT [11]. Concurrent research [14] assessed the freely dissolved fraction of the pesticides CPF and DDT in the presence of DOC at various salinities by using solid-phase microextraction. Results indicated that CPF and DDT sorption to Aldrich HA increased with increasing HA concentration.…”
Section: Humic Acid Mitigation Of Chlorpyrifos and Ddt Toxicitysupporting
confidence: 65%
“…When considering contaminant transport through different salinity regimes in the environment, this interaction could be important. The present research and its companion paper [14] point to the potential impact of the interaction of these factors in contaminant bioavailability and toxicity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation